MALAYSIA- THAILAND CROSSBORDER COMMUNICATION: THE POTENTIAL OF BUSINESS ENGLISH AS LINGUA FRANCA - Suryani, Ina; Desa, Hazry; Yaacob, Aizan (Journal of Human Capital Development (JHCD), 2010)
Recently, with the spread of English as the global language, English has been professed as one of the prominent lingua franca for the new world. It has become the means of communication between nations in the area of judiciary, economic, education and in almost all aspect of global negotiation. Countless studies have been made on the role of English language as a lingua franca; however there is a limited study on the usage of English as lingua franca in crossborder context. It is understood that most people turn to English when communicating across nation, yet it is unclear how English language fare as the lingua franca in crossborder communication especially in South East Asia. Sharing border denoted sharing similar culture, history and exposure and for these similarities it is a wonder if English would still emerge as the language of choice for communication between such parties. This paper analyzes both Malaysian and Thai students’ use of the Business English as Lingua Franca (BELF) during a few crossborder activities held throughout a collaborative project. The findings in this paper suggested that BELF emerged mostly in informal situations for ESL users and as for the formal situations, the ESL users prefer to use the standard English variety. On the other hand, the EFL users use BELF for both formal and informal situations. The EFL users are more inclined to use BELF for both occasions where getting the message across and getting the job done surpassed the concern for English accuracy. ELT implications are cues that English language usage can be encouraged by taking up the following measures such as setting rule on using English for communication, intervening when mother tongue emerges, assigning reports and presentations. In conclusion, this study adds on to the understanding on the role of ELF especially in the context of crossborder communication in South East Asia.\ Keywords: Business English Lingua Franca (BELF), crossborder, mother tongue, communication, lingua franca